The role of diagnostic imaging in the management of invasive fungal diseases: report from an interactive workshop - Gompelmann, Daniela; Heußel, Claus Peter; Schuhmann, Maren; Herth, Felix (Mycoses, 2011)
Invasive fungal diseases are a significant cause of morbidity and mortality in the growing population of immunosuppressed patients. Appropriate early therapy is associated with a reduction in mortality, but relies on rapid diagnosis. Microbiological investigations are often a problem as it can take several days for a culture to mature. As a result, diagnostic imaging techniques play a larger role in the early recognition and characterisation of opportunistic fungal diseases. In April 2009, a 1-day interactive workshop titled ‘The role of diagnostic imaging in the management of invasive fungal diseases’ was held for specialists in haemato-oncology, pneumology and radiology. The aim of the workshop was to show the significance as well as the limitations of diagnostic imaging in the assessment of opportunistic fungal diseases and to provide education as to the radiological findings that aid disease evaluation.
First published: 03 December 2010
Gesehen am 27.06.2022